Shunt Connected FACTS Devices for LVRT Capability Enhancement in WECS - Ganthia, B. P.; Barik, S. K.; Nayak, B. (Engineering, Technology & Applied Science Research, 2020)
When a Double Fed Induction Generator (DFIG) primarily based Type-III Wind Turbine (WT) is connected to the grid without a digital power interface, the terminal voltage or reactive electricity output can’t be managed accordingly. Many techniques have been developed to overcome the issue of low voltage due to faults. This paper tries to define such active methods by presenting a complete analysis of LVRT strategies for DFIG-based Wind Energy Conversion Systems (WECS) in terms of overall adaptive performance, operation complexity of controllers, and cost-effectiveness. This paper aims to highlight the methods of increasing the ability of LVRT relying on the configuration of the relationship into 3 major areas according to its grid integrations. Shunt connections of FACTS devices are used in WECS to study their effectiveness and benefits. The system models are simulated in MATLAB/Simulink and the results are discussed.